UTAUT and In-App Purchase: Revealing Factors Driving Users to Switch to the Premium Version in Online Dating Apps - Ginting, Diyanti Pratiwi; Gayatri, Gita (ASEAN Marketing Journal, 2024)
This study aims to understand the factors influencing purchase intention in premium online dating applications. The main focus is on performance expectancy, effort expectancy, privacy risk, habit, enjoyment, social value, and quality. Data was collected through an online survey in March 2023 with respondents residing in Indonesia. The research method used is descriptive quantitative, based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The variables in this study were measured using a 5-point Likert scale. The sample consisted of online dating app users who had never subscribed to the premium version and had been using the app for the past year. The results showed that performance expectancy, effort expectancy, and enjoyment significantly influence the continuance intention to use the basic version of the online dating app. Additionally, social value and app quality also showed a significant positive correlation with purchase intention for the premium version. Privacy risk was found to have a negative impact on both continuance intention and purchase intention. The discussion highlights the importance of understanding user preferences in online dating applications to develop effective marketing strategies. These findings are expected to help online dating app developers improve service quality and user experience, and provide insights for researchers and practitioners on the factors influencing purchase intention in the digital context.